The Hunger Games spectacle, risk and the girl action hero - Driscoll, Catherine; Heatwole, Alexandra (Routledge, 2018)
"This book considers "The Hunger Games" as an intertextual field centred on this blockbuster film franchise but also encompassing the successful novels that preceded them and the merchandised imagery and the critical and fan discourse that surrounds them. It emphasizes the place of "The Hunger Games" in the history of youth-oriented cinema, in the history of speculative fiction centred on adolescents, in a network of continually evolving and tightly connected popular genres, and in the popular history of changing ideas about girlhood from which a successful action hero like Katniss Everdeen could emerge."--Provided by publisher
Keywords: Collins, Suzanne / Hunger Games (Series); Hunger Games (Motion picture); Hunger Games / Catching fire (Motion picture); Hunger Games / Mockingjay, Part 1 (Motion picture); Hunger Games / Mockingjay, Part 2 (Motion picture); Hunger Games films / History and criticism; Girls in motion pictures; Motion pictures / Social aspects; Young adult fiction, American / History and criticism